Efeito de bioestimulante no desenvolvimento inicial de plântulas do porta-enxerto cítrico tangerineira ‘Cleópatra’ - Souza, Jackyson Mirellys Azevedo [UNESP]; Gonçalves, Bruno Henrique Leite [UNESP]; Santos, Adelana Maria Freitas [UNESP]; Ferraz, Rafael Augusto [UNESP]; Leonel, Sarita [UNESP] (My University, 2013)
Obtaining the rootstock is one of the time consuming steps in the production chain of citrus seedlings, due to the time required for seed germination and early seedling development. In this context, the objective was to evaluate the effects of the use of plant growth regulator on initial seedling rootstock citrus mandarin "Cleopatra". The treatments were related to the concentrations of the commercial product Stimulate ®: control (without plant growth regulator), 6, 12, 18, 24 and 30 mL.kg-1 seed. The seeds were sown in trays of 72 cells. After 70 days of germination, the following characteristics were evaluated: length (cm) and diameter (mm) of the stem, number of leaves, leaf area (dm2 ), dry weight of leaf, stem and root (g), root length (cm) and concentration of chlorophyll "a", "b" and total (mg.m-2 ). The application of Stimulate ® growth at a dose of 6 mL.kg-1 promoted the growth of seedlings of citrus rootstock 'Cleopatra' mandarin, and its use is promising, leading to a reduction in production time rootstock focus on achieving grafting.

A obtenção do porta-enxerto é uma das etapas que demanda tempo na cadeia de produção de mudas cítricas, devido ao tempo necessário para germinação das sementes e desenvolvimento inicial das plântulas. Neste contexto objetivou-se avaliar os efeitos do uso de bioestimulante no desenvolvimento inicial de plântulas do porta-enxerto cítrico tangerineira “Cleopatra”. Os tratamentos utilizados foram correspondentes às concentrações do produto comercial Stimulate ®: testemunha (sem bioestimulante), 6, 12, 18, 24 e 30 mL.kg-1 de sementes. As sementes foram semeadas em bandejas de 72 células. Após 70 dias da germinação, foram avaliadas a seguintes características: comprimento (cm) e diâmetro (mm) do caule, número de folhas, área foliar (dm2 ), massa seca de folha, caule e raiz (g), comprimento da raiz (cm) e teores de clorofila “a”, “b” e total (mg.m-2 ). A aplicação do bioestimulante Stimulate®, na dose de 6 mL.kg-1 promoveu o crescimento das plântulas do porta-enxerto cítrico tangerineira “Cleópatra”, sendo seu uso promissor, promovendo a diminuição no tempo de produção do porta-enxerto visando a realização da enxertia.
Effect of plant growth regulator in the initial development of seedlings of citrus rootstock 'Cleopatra'
Keywords: Citrus reshni; Growth regulator; Citrus seedlings; Citrus reshni; Regulador vegetal; Mudas cítricas